Wpływ specustawy ukraińskiej na sytuację prawną migrantów przymusowych z ukrainy na polskim rynku pracy - Marcin Górski (University of Warsaw, Centre of Migration Research (CMR), 2023)
– This paper, which is an expert opinion commissioned by the Migration Research Centre of the University of Warsaw, concerns the legal conditions resulting from the so-called of the Ukrainian Special Act, for persons covered by the scope of the Act to take up employment on the territory of the Republic of Poland. It includes as well an analysis of the situation of those persons who were granted temporary protection on the basis of an Implementing Decision of the EU Council, but were not covered ratione personae by the Act. Particular attention was paid to the legal situation of persons employed in the domestic work sector and on the basis of a harvesting contract (so-called farmers' assistants). In this paper, sreference was also made to the Ukrainian legal regulations concerning taking up employment by foreigners in Ukraine.
Keywords: 330; ochrona tymczasowa; specustawa ukrainska; zatrudnienie; Temporary protection; Ukrainian Special Act; employment